Design and synthesis of polyimide – Gold nanofibers with tunable optical properties. (March 2015) - Serbezeanu, Diana; Popa, Ana Maria; Sava, Ion; Carja, Ionela-Daniela; Amberg, Martin; Rossi, René Michel; Fortunato, Giuseppino
Graphical abstract: Highlights: Phenol-functionalized polyimide composite nanofibers were developed. Nanofibers were functionalized by gold nanoparticles. Embedded and monodispersed gold nanoparticles are revealed with diameters between 9 and 22 nm. Optical properties of the composite fibers can be tuned according to thermal annealing parameters. Abstract: Aromatic polyimides possess high thermal stability, flexibility, good chemical resistance, mechanical strength, enhanced dielectric properties, being thus widespread used in electronic and microelectronic industry or as a support in high temperature applications. Herein, a soluble functional polyimide with pendant phenol groups was synthesized and its potential to stabilize gold nanoparticles was highlighted by comparison with an aromatic polyimide with similar backbone but lacking the phenol units. Furthermore, composite nanofibers based on the polyimide bearing phenol units and gold nanoparticles were prepared by using an in-situ e-spinning approach. Electrostatic spinning revealed homogenous fiber formation with diameters in the range of 0.28–0.77 μm for pure polyimide, whereas for gold containing polyimide beaded fiber morphologies with diameters in the range of 50–60 nm were determined. A clear influence of the solution properties was measured regarding fiber diameters. Thermal treatment of the composite nanofibers yielded highly dispersed embedded metallic gold particles exhibiting diameters in the range of 9–22 nm, with an increase in particle diameters by enlarging the thermal exposure time. The thermal stability of the composite nanofibers was evaluated by thermogravimetric analysis (TGA) and only a slight decrease in the decomposition temperature in comparison to the pristine polyimide-based nanofibers was observed. Finally, we investigated the effect of thermal treatment on the optical properties of the new nanofibers and we revealed the possibility of tuning the reflective characteristics of the nanofibrous surfaces in function of the annealing time.